Eficacia del uso de PRF en la cicatrización del alveolo post exodoncia dentaria simple y compleja en la clínica estomatológica de Moche de la Universidad Nacional de Trujillo, 2016. - Horna Torres, Katherine (2019)
ABSTRACT The present study was prospective and comparative study of longitudinal cut which consisted in 72 patients of whom were 21 women,15 men (experimental group) and 25 women, 11 men (control group) attending the Dental Clinic of Moche that required treatments of dental extractions dental simple and complex. Objective: To determine the efficacy of the use of PRF in the healing of alveolus post extraction dental simple and complex in the Dental Clinic of Moche of the National University of Trujillo. Material and method: Inclusion criteria were: People with apparent good general health ASA I, with indication of exodontia simple and complex in parts unirradiculares, multirradiculares and people who accepted to participate in the investigation, by signing the cons ent or settlement informed. The age was < 40 and ≥ 40 there were 36 patients with PRF (two clots and two membranes in each alveolus) and 36 patients without PRF between men and women. Results: Compared to the two groups, the expermiental group (with PRF) o btained in simple exodontics (92.1%) and composite (82.4%) where it was effective (p<0.001) with respect to the control group (without PRF) in simple exodontics (44.4%) (44.4%). At 7 days an index was obtained in the experimental group:good(25%), very good (47.2%) and excellent (28%) and the group controls an index:poor(19.4%), good(66.7%) and very good(13.9%).At 14 days an index was obtained in the experimental group: very good(8.3%) and excellent (91.7%) and the group controls an index: good(25%), very goo d(58.3%) and excellent (16.7%). Finally, it tells us that there is a significant association between the Landry Healing Index with the age of <40 years in the experimental group (With PRF) at 7 days and with the age of >=40 years in patients in the control group (without PRF) at 14 days. Conclusion: The technique of handling of plasma rich in Fibrin used in our study was effective in the healing of soft tissues, where it owns effect regenerative braking on the alveolus post exodontia simple and complex demo nstrated clinically at 7 and 14 days according to the index of Landry.